Status de conservação de espécies quiropterófilas endêmicas do Brasil ocorrentes na Caatinga - Oliveira, Hadassa Carolinny Soares de (2023)
The Caatinga stands out for having a significant number of plant-nectarivorous bat interactions. Chiropterophilous plants from the Caatinga belong to the families Acanthaceae, Bromeliaceae, Cactaceae, Capparaceae, Convolvulaceae, Fabaceae, Malvaceae and Passifloraceae. In recent years, this phytogeographic domain has been undergoing a constant process of degradation, due to human actions that affect the natural dynamics of these mutualistic interactions. With this work we aimed to evaluate the conservation status and risk of extinction of 16 species of chiropterophilous plants from the Caatinga. Furthermore, we sought to estimate the decline in distribution areas and the main types of threats that affect these plants over the last 36 years. To do this, we used the list of chiropterophilous plant species occurring in the Caatinga, available in Domingos-Melo et al. (2023). We produced a database with collection locations that were collected from the GBIF (Global Biodiversity Information Facility), Reflora and SpeciesLink online databases. We categorized the risk of extinction of endemic species in Brazil according to IUCN categories and criteria, using criterion B (restricted geographic distribution and showing fragmentation, decline or fluctuations). In our results, we observed that approximately 80% of the species assessed had their conservation status upgraded to extinction risk categories. We verified that the species Encholirium splendidum and Ipomoea vespertilia are categorized as endangered species (EN) and the species Vriesea limae is classified as Vulnerable (VU). We also reveal that these species are subject to different anthropogenic impacts from land use and are threatened, mainly, by pastures, mosaics of uses and urban expansion. Therefore, this study provides important information on the conservation status of 16 species of chiropterophilous angiosperms occurring in the Caatinga, helping to fill gaps in unevaluated species.